Floral Biology and Stigma Receptivity in Bauhinia variegata Linn. - Wani, Afaq Majid; Chauhan, K. C. (Indian Forester, 2008)
Bauhinia variegata bore whitish pink flowers on one year old shoot growth during March-April. The duration of flowering ranged from 26-49 days. Mean time taken to flower bud development was found to be between 20.88 to 24.92 days. The maximum anthesis and anther dehiscence was observed between 7:00 to 8:00 am and 7:30 to 8:30 am, respectively. The average size of pollen grains was found 68.97 Î¼m. In-vivo stigma remained receptive with effect from 2 hrs before anthesis to 8 hrs after anthesis (88.89%).